2015
DOI: 10.3899/jrheum.150097
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Outcomes of Takayasu Arteritis with Neurological Symptoms in China: A Retrospective Study

Abstract: Neurological features in patients with TA were variable, and correlated with the number of arteries and the site of artery involvement. Resistant hypertension was one of the most important risk factors for hemorrhagic stroke in patients with TA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 27 publications
3
15
2
Order By: Relevance
“…In a Chinese study, neurological features in patients with TA were variable and correlated with the number of arteries and the site of involvement. Resistant hypertension was one of the most important risk factors for hemorrhagic stroke in patients with TA [48]. We also observed more hypertension in the "stroke" group, although the difference was not statistically significant.…”
Section: Stroke and Cardiovascular Risk In Tacontrasting
confidence: 46%
“…In a Chinese study, neurological features in patients with TA were variable and correlated with the number of arteries and the site of involvement. Resistant hypertension was one of the most important risk factors for hemorrhagic stroke in patients with TA [48]. We also observed more hypertension in the "stroke" group, although the difference was not statistically significant.…”
Section: Stroke and Cardiovascular Risk In Tacontrasting
confidence: 46%
“…A restenosis rate of 4.5% in another group of patients was observed (Sharma et al, unpublished data). In the present study, only 5 patients (5/46, 10.9%) developed ISR after a follow‐up of 3.1 ± 1.8 years, which was low when compared with similar studies on aorta and other peripheral arteries involving TA , especially considering the long follow‐up duration. Moreover, repeat endovascular therapy for patients with ISR was minimally invasive and effective, which had more advantages than surgical methods.…”
Section: Discussioncontrasting
confidence: 87%
“…TA mainly affects large-caliber arteries such as the aorta and its major branches in patients younger than 40 years old (more than 90% of patients are younger than 40), with a female predominance (female to male ratio is 10:1), and is more common in Asians (1). Studies have shown that more than half of patients with TA show neurological manifestations (15, 16) that range from dizziness/headaches to ischemic or hemorrhagic stroke.…”
Section: Large-vessel Vasculitismentioning
confidence: 99%
“…Dizziness and headache are the most common complaints in patients with TA with neurological complications, accounting for ~78.1% (214/274) and 25.5% (70/274), respectively (16). However, headache and dizziness do not necessarily indicate CNS involvement.…”
Section: Large-vessel Vasculitismentioning
confidence: 99%
See 1 more Smart Citation